ASPEK IMUNOLOGI SLE - -, Yuriawantini; Suryana, Ketut (journal of internal medicine; Vol. 8, No. 3 September 2007, 2012)
Systemic Lupus Erythematosus (SLE) is autoimmune disease characterised by the production of autoantibodies to component of the cell nucleus in association with a diverse array of clinical manifestations. The patho-aetiology of systemic Lupus Erythematosus probably involves multifactorial interaction among various genetic and environmental factors. Multiple genes contribute to disease susceptibility, including genes encoding complement and other components of the immune response. The interaction of sex, hormonal millieu and the hypothalamus-pituitary-adrenal axis modifies this susceptibility and the clinical expression of the disease. Defective immune regulatory mechanism, such as the clearance of apoptotic cells and immune complexes, are important contributors to the development of SLE. The loss of immune tolerance, increase antigenic load, excess T cells helper, defective B cell suppression, and the shifting of T helper 1 (Th1) to Th2 immune responses leads to the B cell hyperactivity and the production of pathogenic autoantibodies. ANAs are antibodies against both functional and structural in the cell nucleus. ANA is early detection of autoantibodies for the patient with clinical features that suggest SLE. Positive test for antinuclear antibodies may support the diagnosis, especially if more spesific autoantibodies are present, such as anti-double-stranded DNA, anti-Sm, anti-RNP or anti-Ro. Understanding the value of autoantibody testing in patient care requires clinical judgment and experience.
Keywords: systemic lupus erythematosus, immune respons